The Zebrafish (Danio rerio): A Dynamic Model Organism for Scientific Research - Alla, Rama Krishna; Konakanchi, Anusha; Nallakunta, Rajesh; A. V., Ramaraju; M. C., Suresh Sajjan; Mantena, Satyanarayana Raju (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Zebrafish has become a fundamental model organism in biomedical research due to their genetic similarity to humans, rapid development, and transparent embryos. In developmental biology, zebrafish provides insights into embryogenesis, organogenesis, and genetic manipulability. They offer a unique platform for studying vertebrate development and understanding genetic functions through genome sequencing and gene editing techniques. Zebrafish is valuable in disease modelling, particularly in cancer research, neurological disorders, cardiovascular diseases, and infectious diseases. Their regenerative capabilities in tissues like the heart, fin, and spinal cord make them crucial in regenerative medicine studies. Furthermore, zebrafish serves as bioindicators in environmental and ecological studies, assessing the impact of environmental pollutants and behavioural ecology changes. Technological advancements, especially in imaging techniques and genomic resources, have expanded the scope of zebrafish research. Emerging areas like microbiota-host interactions, precision medicine, and artificial intelligence integration hold promise for future discoveries and applications. This review explores the biological characteristics of zebrafish and their significance in various research domains.